A catalogue of verified and characterized arterial enhancers for key arterial identity genes - Nornes, S; Bruche, S; Adak, N; McCracken, I; De Val, S (2024)
The establishment and growth of the arterial endothelium requires the coordinated expression of numerous genes. However, the transcriptional and signalling pathways regulating this process are still not fully established, and only a small number of enhancers for key arterial genes have been characterized. Here, we sought to generate a useful and accessible cohort of arterial enhancers with which to study arterial transcriptional regulation. We combined in silico analysis with transgenic zebrafish and mouse models to find and validate enhancers associated with eight key arterial identity genes (Acvrl1/Alk1, Cxcr4, Cxcl12, Efnb2, Gja4/Cx37, Gja5/Cx40, Nrp1 and Unc5b). This identified a cohort of enhancers able to independently direct robust transcription to arterial ECs within the vasculature. To elucidate the regulatory pathways upstream of arterial gene transcription, we determined the occurrence of common endothelial transcription factor binding motifs, and assessed direct binding of these factors across all arterial enhancers compared to similar assessments of non-arterial-specific enhancers. These results find that binding of SOXF and ETS factors is a shared event across arterial enhancers, but also commonly occurs at pan-endothelial enhancers. Conversely, RBPJ/Notch, MEF2 and FOX binding was over-represented but not ubiquitous at arterial enhancers. We found no shared or arterial-specific signature for canonical WNT-associated TCF/LEF transcription factors, canonical TGFβ/BMP-associated SMAD1/5 and SMAD2, laminar shear stress-associated KLF factors or venous-enriched NR2F2 factors. This cohort of well characterized and in vivo-verified enhancers can now provide a platform for future studies into the interaction of different transcriptional and signalling pathways with arterial gene expression.